(untitled) (Transport systems and technologies, 2022)
The type and characteristics of such cargo as iron ore pellets are described. The manufacturing technique of iron ore pellets at the mining processing plant is given. The process of transporting iron ore pellets along the main tracks of JSC "Ukrzaliznytsia" to the consumers of these products was considered using the example of PJSC "Poltava Mining and Processing Plant". It has been established that iron ore pellets are transported on the main railway tracks by one of the following types of freight wagons: universal gondola cars with a hollow-bottom body or discharge doors, specialized hopper wagons for the transportation of pellets and agglomerate and mainline dump cars. A comparative analysis of the efficiency of the use of the specified types of freight wagons was carried out according to such technical and economic indicators (criteria) as tare weight, carrying capacity, car body volume, material intensity, specific volume, dimensions, service life time, overhaul life, tare loading coefficient, coefficient body capacity utilization, running load, cost, life cycle cost. It was determined that the most rational option for the transportation of iron ore pellets is the use of a universal gondola car. Further research should be directed to the development of a standard-sized series of specialized freight wagons with increased linear load and improved technical and economic indicators for the transportation of iron ore pellets based on a universal gondola car. The content of the article will contribute to the rational choice of freight rolling stock for the transportation of such kinds of cargo as iron ore pellets on mainline railways.